The Drosophila TNF ortholog Eiger: Emerging physiological roles and evolution of the TNF system. - Igaki, T.; Miura, M. (Seminars in Immunology, 2014)
The TNF and TNFR superfamilies of proteins are conserved throughout evolution. The first invertebrate orthologs of TNF and TNFR, Eiger and Wengen, were identified in Drosophila, which enabled us to take advantage of its powerful genetics. Indeed, genetic studies on Eiger in the last decade have discovered their signaling mechanisms through activation of the JNK pathway and unveiled the role of Eiger-JNK signaling in a variety of cellular and tissue processes such as cell death, cell proliferation, tissue growth regulation, host defense, pain sensitization, and canalization. In this review, we will describe the in vivo signaling of Eiger and its physiological roles in fly development and homeostasis, and will discuss the evolution of the TNF/TNFR systems.